(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The CoViD-19 pandemic has promptly brought together the social and individual aspects of the right to health, highlighting some issues that are typical of the healthcare service: nosocomial contagion risk and cure decision against the backdrop of disequilibrium between health needs and available resources. The essay tackles these matters in light of the civil liability system outlined within the law n. 24/2017, putting forward some integrative proposals of the protection framework.